TEACHING NON VERBAL COMMUNICATION IN TEACHING LEARNING PROCESS AT SMP NEGERI ROBATAL SAMPANG - Wildona Zumam; Mahfud Mahfud (The Ellite of Unira, 2022)
The teacher is not only used verbal communication but also used nonverbal communication, this article aims to investigate the teacher use nonverbal communication in teaching learning process and the teachers’ nonverbal communication effect on the classroom atmosphere at SMP Negeri 2 Robatal Sampang. The subjects of the study are the teacher and the students. The instruments used to get the data were observation, interview and documentation. The results of the shows that the teachers’ nonverbal used in teaching learning process are hands, space and distance, touching and chronemics. Beside that the effect of nonverbal communication used were helping students understanding and accompanying to verbal message. Helping students understanding more easily to a students to receive the material that’s explains by the teacher. Accompanying to verbal message is a student’s more easily understand to get the point of teachers’ explanation in teaching learning process..